Strengthening Libor and Rate-Setting Processes: Recommendations for Policymakers (Global Journal of Management and Business Research, 2015)
The authors present two different models to better understand and analyze the recent Libor scandal. These models can be applied generally to other rate-setting processes and can be used by policymakers and regulators to effectively monitor benchmarks for manipulation
Keywords: monitor benchmarks for manipulation